2007
DOI: 10.1093/toxsci/kfm050
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Scavenger Receptor MARCO Recognizes Polystyrene Nanoparticles

Abstract: Recent toxicological studies indicate that nanoparticles or ultrafine particles (< 100 nm) are more toxic than fine particles (< 2 microm) because of their greater surface area. It is well known that alveolar macrophages play an important role in the first defense against various environmental particles and microorganisms. This is accomplished by binding to a macrophage receptor with collagenous structure (MARCO), one of several scavenger-type receptors expressed on the cell surface of macrophages. MARCO has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 29 publications
6
76
0
1
Order By: Relevance
“…Opsonin-independent receptors include scavenger receptors which bind to a variety of substances, including modifi ed lipoproteins. Macrophage receptor with a collagenous structure (MARCO), a class A scavenger receptor, can bind gram-negative and gram-positive bacteria and has been suggested to be involved in the uptake of polystyrene particles [34]. Many opsonin-independent receptors bind to conserved microbial structures.…”
Section: Macrophage Phagocytosismentioning
confidence: 99%
“…Opsonin-independent receptors include scavenger receptors which bind to a variety of substances, including modifi ed lipoproteins. Macrophage receptor with a collagenous structure (MARCO), a class A scavenger receptor, can bind gram-negative and gram-positive bacteria and has been suggested to be involved in the uptake of polystyrene particles [34]. Many opsonin-independent receptors bind to conserved microbial structures.…”
Section: Macrophage Phagocytosismentioning
confidence: 99%
“…These pattern recognition molecules mediate recognition and uptake of foreign material and modified host molecules (e.g., oxidized proteins and lipids) and exhibit a large array of ligand specificity. Lung macrophages use scavenger receptor A (SRA)-1 and macrophage receptor with collagenous structure (MARCO) to mediate uptake and clearance of lung pathogens, Streptococcus, unopsonized micro-and nanoparticulate matter, and ozonegenerated oxidized lipid intermediates (15)(16)(17)(18)(19). In all these studies, MARCO 2/2 mice showed increased morbidity or mortality because of decreased macrophage-mediated uptake and clearance, leading to exacerbated neutrophil response and enhanced lung pathology.…”
mentioning
confidence: 99%
“…To test the hypothesis that enhanced oxidative stress associated with Nrf2 deficiency impairs the clearance of respiratory infections, we identified a previously unknown role of Nrf2 in regulating expression of the scavenger receptor macrophage receptor with collagenous structure (MARCO). MARCO aids in the binding and uptake of bacteria, oxidized low-density lipoproteins, and environmental particles (42,43). MARCO is highly expressed in tissue (liver or lung) macrophages in response to bacterial infection, and genetic ablation of MARCO enhances bacterial colonization, inflammation, and diminished survival in a model of pneumococcal pneumonia (43).…”
Section: Targeting Nrf2: Experimental Therapeutics For Preventing Acumentioning
confidence: 99%